ENHANCING CLINICAL TEACHING: EVALUATING THE ONE MINUTE PRECEPTOR MODEL IN RADIOLOGY EDUCATION - Salakay, Elisa Nugraha Haryadi; Mahu, Grace Fitriana Primasari Hau; Astawa, Gregorius Adista Enrico; Rumbino, Samdei Carolina; Tamher, Astuti (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: Clinical education in radiology often faces challenges due to time constraints and the passive nature of conventional teaching methods, which hinder the development of students' diagnostic reasoning. The One Minute Preceptor (OMP) model offers a structured, learner-centered teaching approach that may address these gaps, particularly in time-limited settings.Objective: This study aimed to evaluate the effectiveness of the OMP model compared to conventional teaching methods in improving the knowledge of radiographic interpretation and diagnosis among medical students during their clinical rotation in the Radiology Department at Universitas Cenderawasih (FK Uncen).Methods: A quasi-experimental pre-test post-test nonequivalent control group design was used. Sixty professional medical students were purposively assigned to either the OMP group or the conventional group (lectures and observation), with 30 students in each. Group allocation was based on comparable cumulative GPA and clinical activeness to ensure balanced academic performance between groups. Over a one-week intervention, both groups were exposed to the same thoracic radiology cases. The OMP group received instruction following the five microskills framework, eliciting commitment, probing for evidence, teaching general rules, reinforcing correct responses, and correcting mistakes, while the control group received conventional lectures followed by tutor-led discussions without structured feedback. Knowledge improvement was measured using validated multiple-choice questions administered before and after the teaching session. Data were analyzed using independent sample t-tests and normalized gain (N-Gain) scores.Results: Both groups showed improvement in post-test scores. The OMP group had a higher mean post-test score (71.30 vs. 63.73) and mean N-Gain (29.06 vs. 23.70), although the differences were not statistically significant (p = 0.363). These findings are consistent with trends reported in international literature, which support the use of OMP in enhancing diagnostic learning outcomes.Conclusion: While not statistically significant, the OMP method showed a trend of greater improvement in radiographic diagnostic knowledge compared to conventional teaching. This pilot study supports the feasibility and potential of OMP as an effective instructional model in radiology education within the Indonesian clinical teaching context, warranting further research with larger samples and extended durations.